Analysis of Factors Influencing the Rupiah Exchange Rate against the United States Dollar for the 2004-2021 Period - Zaliyanty, Istia; Soebagyo, Daryono (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
The purpose of this study was to determine the independent variables, namely inflation, interest rates, money supply, and exports in influencing the rupiah exchange rate against the US dollar using multiple linear regression analysis using the Ordinary Least Square (OLS) method. The results in this study indicate that jointly the independent variables have an effect on the rupiah exchange rate against the US Dollar for the period 2004 to 2021. Meanwhile, individually the inflation and interest rate variables have a positive and insignificant effect on the rupiah exchange rate against the US Dollar. Then, the variable money supply and exports have a significant impact, but only exports have a negative effect on the rupiah exchange rate against the US dollar. With a value of 92.2%, the dependent variable, namely the rupiah exchange rate against the US Dollar, can be explained by inflation, interest rates, money supply, and exports with a value of 92.9%. In addition, the remaining 7.1% can be influenced by variables or factors not included in the model